Determination of Initial Lag and Maximum Lag Distance of Semivariogram on Reserves Calculation of Gold Vein - Nur Ali Amri; Abdul Aziz Jemain; Wan Fuad Wan Hassan; Hasywir Thaib Syiri (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2015)
The reserves calculation is one of the early stages before the mining operation, which begins with thesamples prediction. Ordinary kriging is a part of the kriging method that works with semivariogramparameters. The calculation of these parameters based on several things, including thedetermination of the lag distance and the fitting model. This paper is based on the determination of themaximum lag distance of 500 and 800 where the lag distance for both, respectively 15, 25 and 35 withWLS and OLS fitting models. The six combinations can be concluded that increasing of maximumlag distance adds to a large of sill and extend the range. OK prediction shows that the largest goldgrade mean (5.032) occurs in the kriging using WLS fitting models, in which the maximum lag distancesemivariogram is 500 and the distance of each lag is 35.